PENGARUH PROGRAM PENSIUN DAN PROGRAM K3 TERHADAP SEMANGAT KERJA DAN PRESTASI KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA V SEI GALUH KABUPATEN KAMPAR PROVINSI RIAU - Mahmud Badri Amirul; Ningsih Suryati Dewita; Fitri Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study was undertaken at PT. Perkebunan Nusantara V, Kampar Regency. The aim of this study was to discover the effect of the pension program and K3 program variable partially or simultaneously on the work enthusiasm and work performance of employees of PT. Perkebunan Nusantara v Kampar Regency. This study was conducted with a special method on 74 employees who were sampled. The research variables used were the pension program and the occupational health & safety program as independent variables, and work enthusiasm and work performance as the dependent variable. The data analysis method used was path analysis using SPSS 23 for windows. The findings indicated that the pension program variable and the occupational health & safety program variable partially or simultaneously had a significant effect on work enthusiasm and work performance of employees, the result of the coefficient of determination (R2) was 0, 803, it implied that the percentage of the effect of the pension program and occupational health & safety program on work enthusiasm and work performance was 80.3%. While the remaining of 19.7% was influenced by other variables that were not included in this path.Keywords: Pension Program, K3 Program, Work Enthusiasm and Work Performance of Employees